2021
DOI: 10.3390/w13233386
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Water Resources and Water Environmental Carrying Capacity of Animal Husbandry in China—Based on Water Footprint Theory

Abstract: Water shortage and water pollution have become the key factors restricting the sustainable development of animal husbandry in China. In this study, the water footprint model was used to analyze the water resource carrying capacity and water environment bearing pressure of animal husbandry in 31 provinces of China from 2001 to 2019. The findings indicate that: (1) The development of animal husbandry has exacerbated the regional water deficiency problem. Shandong, Henan, Hebei, and Liaoning have become the most … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 6 publications
0
9
0
Order By: Relevance
“…Wei et al (2022) study found that the accelerated expansion of cities in the middle of the study area, and the habitat quality has also declined. Yu et al (2021) found that regional heterogeneity of water resources severely limits the development of animal husbandry. Specifically, western areas of the study areas mostly suffered from desertification and grassland desertification.…”
Section: Spatiotemporal Heterogeneity Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Wei et al (2022) study found that the accelerated expansion of cities in the middle of the study area, and the habitat quality has also declined. Yu et al (2021) found that regional heterogeneity of water resources severely limits the development of animal husbandry. Specifically, western areas of the study areas mostly suffered from desertification and grassland desertification.…”
Section: Spatiotemporal Heterogeneity Analysismentioning
confidence: 99%
“…Jayaraman and Nyachoti (2016) approached the subject from the perspective of livestock breeding and proposed that the effectiveness in breeding could be the key to a healthy livestock development. Liu et al (2022a) and Yu et al (2021) considered that the development of animal husbandry was, to some extent, affected by demographic factors. Influenced by global warming, climate in many regions had changed greatly, which could directly affect vegetation dynamics and biomass.…”
Section: Introductionmentioning
confidence: 99%
“…The pH value of mine water is often low, accompanied by a large number of ferrous ions, which increases the difficulty of its treatment. The water quality characteristics of mine water with high calcium and magnesium ions, high carbonate ions, and high sulfate ions will cause it to be very easy to scale in the circulating cooling system, where the formation of sulfate scale is difficult to be removed by conventional methods 1–8 …”
Section: Introductionmentioning
confidence: 99%
“…The water quality characteristics of mine water with high calcium and magnesium ions, high carbonate ions, and high sulfate ions will cause it to be very easy to scale in the circulating cooling system, where the formation of sulfate scale is difficult to be removed by conventional methods. [1][2][3][4][5][6][7][8] In circulating cooling water systems, the following types of scale may be generated: carbonate scale, sulfate scale, and silicate scale.…”
Section: Introductionmentioning
confidence: 99%
“…The studies evaluating carbon footprints of pig production have also been conducted in numerous countries, such as Canada (Vergé et al 2016), Argentina (Arrieta and González 2019), Spain (Noya et al 2016), and Italy (Bava et al 2017). Given the significant water consumption of pig production, previous studies have also analyzed water footprint from various perspectives, such as carrying capacity (Yu et al 2012), trade (Zhuo et al 2019), farming scale (Xie et al 2020), and water use efficiency (Zhang et al 2022). The study of carbon emissions from pig farming is often combined with land use (Meul et al 2012, Monteiro et al 2019.…”
Section: Introductionmentioning
confidence: 99%